Induction of short gut syndrome and transplantation in a porcine model - Llanos, Juan Carlos [UNESP]; Bakonyi Neto, Alexandre [UNESP]; Lerco, Mauro Masson [UNESP]; Clark, Rosana Maria de Oliveira [UNESP]; Valle, Adriana Polachini do [UNESP]; Sousa, Marcelo Magno de Freitas [UNESP] (Elsevier, 2006)
Experimental models in small animals have been described for nutritional studies after small bowel transplantation for extensive resection. Herein, we compared the outcome of transplanted pigs that underwent transplantation after total small bowel resection (SBR) with controls without transplantation. Twenty-one Landrace pigs (mean weight 30 kg) were assigned to 1 of 3 groups: group 1 (n = 6) underwent 80% SBR; group 2 (n = 9), total bowel resection; and group 3 (n = 6) total resection plus small bowel transplantation. Postoperative evaluation included biochemical analyses, weights, and evaluation of clinical status. Conventional endoscopies with graft biopsies were obtained every 4 days to assess rejection. Group 1 showed increased body weight after 3 weeks due to bowel adaptation, whereas groups 2 and 3 lost weight, an observation that correlated with biochemical analyses. Median survival in group 3 was 10 +/- 2 days; all hosts died of sepsis related to severe acute rejection. Short gut syndrome appeared in group 2 but not in group 1, where intestinal adaptation was observed by 4 weeks after the resection. Rejection was confirmed in group 3 using conventional endoscopy plus biopsies and at necropsy. Total bowel resection is an adequate model for short gut syndrome in pigs, rejection can be readily identified by using conventional endoscopy.